PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS DAN FINANCIAL LEVERAGE TERHADAP PRAKTIK PERATAAN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Fatmawati .; Atik Djayanti (KELOLA, 2015)
This research aimed to analyze the influence of company size, profitability, and financial leverage on earnings smoothing practice at companies listed in Indonesia Stock Exchange. A number of samples are the 22 manufacturing companies and generate 132 observations. These samples are chosen by purposive sampling method since 2009 up to 2011. Earning smoothing practice calculated with Eckel Index. This Index is a model that can estimate that company done earnings smoothing practice. It is calculated from deviation standard of income delta to sales delta. Analyzing use binary Logistic regression because the dependent variable is a dummy. Goodness of fit test used hosmer and lemeshow and the result fit. The outcome of research showed that for partial testing for company size that proxy by the natural logarithm of total assets, profitability proxy by Return on Assets (ROA) and Financial Leverage proxy by Debt to Total Assets (DTA) individually significant influence the practice of smoothing earnings. Simultaneous testing used the omnibus test also reached the same conclusion. Keywords: company size, profitability, financial leverage and earnings smoothing practice